Value Stream Mapping: Case Study in a Water Heater Manufacturer - Ali TURKYILMAZ; Ali GORENER; Humeyra Baser (International Journal of Supply Chain Management, 2013)
The value stream mapping is a lean production technique used by Toyota Production System (TPS) to visualize and design flow of information, material and production for analyze non-value added and value added operations. In this paper, the method of value stream mapping (VSM) was revealed by literature investigation and an application in a lean manufacturer firm. It is shown that efforts on effective use of source with prevention of waste source in production and increasing value added (VA) operations. In the first part, value stream mapping technique was explained and literature review presented. Second part includes the application study in the electric water heater line of a manufacturing firm. Value stream maps were drawn and therefore non-value added (NVA) works were determined and they had been eliminated in improved case. And last section of the study showed conclusion of lean implementation.